Pengaruh Kompensasi Terhadap Kinerja Karyawan - Nugraha, Alvi; Tjahjawati, Sri Surjani (Jurnal Riset Bisnis dan Investasi, 2017)
Compensation is an important thing that employees should be given to employees appropriately, whether compensated financially or non-financially compensated. Employees need compensation such as bonuses, benefits, a comfortable working environment, and work that can show the ability for employees to provide the best performance to the company. One of the objectives of this study is to determine the effect of financial compensation on employee performance in Cargill Tropical Palm (ISK Lake View Estate) of West Kalimantan. The sample in this research is all of Cargill Tropical Palm (ISK Lake View Estate) field employee as many as 110 people used as material of analysis. The concept of variable compensation consists of three dimensions including direct, indirect, and non-financial financial compensation. Performance variables consist of quality of work, quantity of work, reliability, knowledge, and cooperation. The analysis used is descriptive analysis. Test validity, reliability, classical assumptions, regression, correlation, and determination. The data obtained is processed using SPSS Statistics 20.0 program and yields the equation Y = 24.662 + 0,543, which means that with increasing compensation of 24,662 it will increase the employee performance of 0,543.